2000
DOI: 10.1002/1097-0282(2000)56:1<1::aid-bip1036>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of the W35A mutant thioredoxinh fromChlamydomonas reinhardtii: The substitution of the conserved active site Trp leads to modifications in the environment of the two catalytic cysteines

Abstract: The conformational analysis of W35A thioredoxin h from the eukaryotic green alga Chlamydomonas reinhardtii in the solid state has been carried out by x‐ray diffraction, with the aim to clarify the role of Trp in the catalysis. Comparative analysis of W35A mutant with wild‐type (WT) thioredoxin shows that, even if the structural motif of thioredoxin is not perturbed, the substitution of Trp35 by an Ala leads to significant changes in protein conformation near the active site. This rearrangement increases its so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…S6). Trp-21 is a very well conserved residue in thioredoxins that is involved in enzyme substrate recognition (49), and Pro-23 is a well conserved residue in the active site motif in the class I glutaredoxins (50).…”
Section: Gst5118 X-ray Structures-two Structures Of Gst5118mentioning
confidence: 99%
“…S6). Trp-21 is a very well conserved residue in thioredoxins that is involved in enzyme substrate recognition (49), and Pro-23 is a well conserved residue in the active site motif in the class I glutaredoxins (50).…”
Section: Gst5118 X-ray Structures-two Structures Of Gst5118mentioning
confidence: 99%
“…47 Indeed, Menchise et al (2001) suggested that the Trp residue at the active site of TRX has a dual function both to force the active site in the bioactive conformation and to mediate protein-protein recognition. 47 We therefore simulated two model complexes of oPtGPX5-TRX h1. The poplar TRX h1 enzyme exhibits an unusual active site with the sequence WCPPC rather than the typical WCGPC motif.…”
Section: Comparison Between Reduced and Oxidized Form Ptgpx5: Redox-dmentioning
confidence: 99%
“…The crystal structures of several thioredoxins have been solved, from E. coli [10,11], human [12], Anabaena [13], Chlamydomonas reinhardtii [14,15] and spinach [16]. In this paper, we report the three‐dimensional structure of T. brucei Trx at 1.4 Å resolution.…”
Section: Introductionmentioning
confidence: 99%